Sequence Based Receivers for Bandlimited Nonlinear Channels - Dubey, Kishore Vimal (My University, 1986)
This thesis examines receiver structures based on maximum likelihood sequence estimation (MLSE) for receiving quaternary phase-shift-keyed (QPSK) signals over bandlimited, non-linear satellite channels, in the presence of additive down link gaussian noise. Two satellite channel models are considered. In the first channel model, the effects of intersymbol interference caused by filtering followed by AM/AM and AM/PM conversions are taken into account while the second channel model includes a post-nonlinearity filter.
An explicit expression for the output of the bandpass nonlinearity (BPNL) for a QPSK signal is obtained in terms of an inphase (1)-quadrature (Q) path memory parameter Pk. The computation of the output of the BPNL requires a knowledge of its transfer characteristic. The transfer characteristics may be specified either analytically or through experimental measurements.
An optimum MLSE receiver structure for bandlimited, non-linear satellite channel is derived and its performance evaluated using computer simulation. Simulating the MLSE receiver in optimum form is too time consuming, so we estimated the I-Q path history parameter pk'S by using a simple procedure analogous to decision feedback processing. Although this method is not theoretically equivalent to an optimum computation, our results show that it performs essentially as well as an optimum computation. For moderate to high SNR, an upperbound on the probability of symbol error is obtained, using the concept of error events. A simplified expression for an upperbound on probability of symbol error, for the case when single-error error events are dominant is also obtained. A sub-optimum receiver structure is then derived using average matched filter responses. The sub-optimum receiver which turns out to be a complex filter followed by a decision device, is a relatively simple structure. The performance of the sub-optimum receiver was estimated for two different uplink filters. The effect of varying the BPNL input drive level was also studied. Our simulation results indicate that the performance of both the MLSE and the sub-optimum receivers approach asymptotically the same optimum performance band.
Finally, we extend our results on an optimum receiver structure for receiving QPSK signals over a digital satellite communications channel, to include the effects of filtering following the non-linear satellite transponder. It is shown that the complexity of the MLSE receiver is primarily determined by the uplink channel memory. The error performance of the receiver at low signal-to-noise ratios is evaluated by computer simulation. An upperbound on the probability of symbol error at moderate to high SNR is also obtained. A sub-optimum receiver similar to the uplink channel filtering case is developed and its performance evaluated using computer simulation. The degradation in performance of the sub-optimum receiver compared to the optimum receiver is found to be small.
Keywords: Electrical and Electronics; Electrical and Electronics